2005
DOI: 10.1016/s0002-9440(10)62040-8
|View full text |Cite
|
Sign up to set email alerts
|

Human Neutrophil Elastase Induces Hypersecretion of Mucin from Well-Differentiated Human Bronchial Epithelial Cells in Vitro via a Protein Kinase Cδ-Mediated Mechanism

Abstract: The presence of mucus obstruction and neutrophil-predominant inflammation in several lung disorders, such as cystic fibrosis, suggests a relationship between neutrophils and excess mucus production. Mechanisms of human neutrophil elastase (HNE)-induced mucin secretion by well-differentiated normal human bronchial epithelial (NHBE) cells maintained in air/liquid interface culture were investigated. HNE increased mucin secretion in a concentration-dependent manner, with maximal stimulation (more than twofold) oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
92
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 58 publications
3
92
0
Order By: Relevance
“…hypersecretion in human bronchial epithelial cells (37,38) and caused mucus metaplasia in mouse lungs (43). It is plausible that mucus metaplasia occurs in CA-IKKb-expressing mice beyond the timeframe of investigation within the current study, which may contribute to potentially chronic abnormalities in respiratory mechanics, although these possibilities remain to be formally tested.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…hypersecretion in human bronchial epithelial cells (37,38) and caused mucus metaplasia in mouse lungs (43). It is plausible that mucus metaplasia occurs in CA-IKKb-expressing mice beyond the timeframe of investigation within the current study, which may contribute to potentially chronic abnormalities in respiratory mechanics, although these possibilities remain to be formally tested.…”
Section: Discussionmentioning
confidence: 88%
“…Therefore, the marked presence of neutrophils might contribute to increases in AHR in CA-IKKb-expressing mice. Neutrophils are capable of generating a number of mediators, such as reactive oxygen and nitrogen species, matrix metalloproteinases, and elastase, which have been linked to increases in AHR directly, or indirectly after stimulation of ASM cells or airway epithelial cells (35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…None of the treatments generated a toxic response in the cells, as assessed by LDH retention/release (data not shown) (28).…”
Section: Cytotoxicitymentioning
confidence: 93%
“…Other factors can also induce mucus. For example, LPS can stimulate low-level mucous production in IL-13-deficient mice (17), and many studies have shown a role for human neutrophil elastase in mucous production (19,20). Even in light of the seminal studies of mucin gene expression by Carol Basbaum (21,22), there is only a rudimentary understanding of how these mediators stimulate mucins, the contribution of different mucins to the protective response, and which pathways are active in human disease.…”
Section: Il-13 Stimulates Mucus In Asthmamentioning
confidence: 99%